1984
DOI: 10.1136/adc.59.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Timing and evolution of periventricular haemorrhage in infants weighing 1250 g or less at birth.

Abstract: SUMMARY The brains of 50 consecutively admitted infants who weighed 1250 g or less at birth were examined with real time ultrasound. Of 30 (60%) who had periventricular haemorrhage (PVH), 19 (63%) bled on the first day and 17 (57%) showed extension of the initial haemorrhage on serial scans. The median age was 16 hours when PVH was first detected and 48 hours when PVH reached its maximum extent. Ventricular size at birth correlated with gestation. Progressive ventricular growth was seen after birth in infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…This accounted for the finding that growth retardation was associated with increased survival in this and another study. 7 The fact that perinatal asphyxia was associated with increased mortality emphasised the importance of prevention or early detection and treatment of asphyxia in the management of extremely preterm labour.…”
Section: Discussionmentioning
confidence: 99%
“…This accounted for the finding that growth retardation was associated with increased survival in this and another study. 7 The fact that perinatal asphyxia was associated with increased mortality emphasised the importance of prevention or early detection and treatment of asphyxia in the management of extremely preterm labour.…”
Section: Discussionmentioning
confidence: 99%
“…Details of perinatal care (Obeyesekere et a!. 1980;Yu 1977;Yu et al 19796, 1981, 19826;Wilson et al 1983) and neonatal complications Yu & Hollingsworth 1979;Yu et al 1979aYu et al , 1982aYu et al , 1983Szymonowicz & Yu 1984) in these infants at QVMC have been reported previously.…”
Section: Methodsmentioning
confidence: 74%
“…The percentage of outborn infants in these published series ranged from 17% to 100% making meaningless any comparison between hospitals because of the profound selection bias that can operate in the transport process (Kitchen et al 1983(Kitchen et al , 1984aSaigal et al 1984). Furthermore, the percentage of small-for-gestational age (SGA) infants ranged from 7% to 51% again suggesting differences in the gestational age of these weight-selected populations, a factor which is known to influence outcome significantly (Yu et al 1984~).…”
mentioning
confidence: 99%
“…In view of current interest to establish the predictive value of perinatal risk factors associated with PIVH, it is of interest to note that previous studies using real-time ultrasound scanning report maximal efficiency for diagnosis of PIVH on day 14 [16,20]. Significant intraventricular hemorrhage may be missed by ultrasound, particularly if ultrasound scan is obtained within few days of the time of hemorrhage since fresh blood may initially appear sonolucent [5].…”
Section: Discussionmentioning
confidence: 99%